One-step fabrication of apatite-chitosan scaffold as a potential injectable construct for bone tissue engineering. (1st January 2019) - Jahan, Kaushar; Mekhail, Mina; Tabrizian, Maryam
Highlights: All-in-one step preparation of an injectable rapid-gelling chitosan-based composite. Gelation time can be tuned by the changing the percentage of bioceramics. Size of the particles affects the porosity but not the viscoelastic properties. Compression tests indicate the characteristics of soft materials are maintained. Abstract: Biomineralization of soft scaffolds is a new venture in bone tissue engineering. This work aimed to develop a new injectable and in-situ gelling soft scaffold with chitosan and apatites through a rapid purine-crosslinking reaction. The scaffolds were fabricated by mixing chitosan, adenosine diphosphate and biominerals in an 'all-in-one-step' procedure. The gelling of chitosan via the crosslinker occurs in <4 s as measured by impedance spectroscopy. These soft gels could retain up to 4 times their weight in water. Spectroscopy showed the formation of ionic bonds between chitosan and the apatites. Morphological analyses revealed an interconnected, highly porous structure, with pore size ranging from 200 nm-200 μm that was maintained even with the biominerals. Rheology showed a viscoelastic behavior of the solutions and the elastic behavior of the sponges, and therefore their injectability potential. in vitro studies showed good cell adhesion and morphology, as well as potential use for bone tissue engineering applications.